210Po concentration in different size fractions of aerosol likely contribution from industrial sources. (October 2020) - Behbehani, M.; Uddin, S.; Baskaran, M.
Abstract: 210 Po, being a highly radiotoxic isotope, could contribute to significant inhalation dose to humans. This study establishes the first set of atmospheric 210 Po data in aerosol samples collected across Kuwait. The primary focus of this study is to investigate spatio-temporal variability of atmospheric 210 Po and assess its sources, including anthropogenic contributions. Measurements of 210 Po in aerosols collected over a period of 23 months (January 2018–November 2019) from three different locations, i.e., a remote area (120 km) north of Kuwait City, Kuwait city and an industrial site (60 km from Kuwait City center). Specific activities of 210 Po were determined in 3 different size fractions (0.39–2.5 μm, 2.5–10 μm and ≥10 μm) and the highest activity was observed in the fine fraction (PM0.39- 2.5 ) across all sampling stations during both the summer and winter seasons. The highest activities in all the size fractions were measured downwind of the Industrial site that houses oil refineries, cement factory and some other industries including a Power and Desalination Plant. In terms of temporal variations, higher summertime activities were observed across the spatial domain. Longer residence time of atmospheric 222 Rn-produced 210 Pb resulting in lower scavenging of atmospheric 210 Pb, due to very little precipitation in summer, will result in higher atmospheric 210 Po. Highlights: Study provides insight on spatio-temporal variability of 210 Po concentration from an oil producing country and is an analog for other arid desert regions in the world. There are large variations in the mass concentrations of aerosols in different size fractions. The downward of Industrial site has the highest 210 Po concentration as well as highest mass of particulate matter. 210 Po in PM≥10  were higher by a factor 2 to 7 compared to the underlying fine terrigenous material (<42 mm) in soil.